PENGGUNAAN SELULOSA-DIETILENTRIAMINA SEBAGAI LAPISAN PENGIKAT LOGAM Cu(II) DENGAN METODE GRADIEN DIFUSI DALAM FILM TIPIS - Khairuddin Khairuddin; Dwi Juli Puspitasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
This researh aims to application of cellulose-diethylenetriamine as a binding layer on the diffusive gradients in thin films method with modification of cellulose with diethylenetriamine. The method of diffusive gradients in thin films in principle uses a simple instrument such as round plastic with a diameter of 2.5 cm, which is filled with metal binding gel, diffusive gel, and membrane filter of 0.45 µm. The metal ions were diffuse through the membrane filter and diffusive gel according to the Fick's Law I, and then is accumulated in the binding layer gel. Based on the results of FTIR analysis, the formation of the binders of the copper ions at the binding layer of cellulose-dietilentriamina involves amine and hydroxyl functional groups.The results of the application of cellulose- diethylenetriamine using as binding layer with polyacrylamide diffusive gel showed a liniar concentration up to 12 hours of contact time and initial copper ion concentration up to 1000 mg/L. The maximum concentration of copper was obtained at pH 4.Keywords: copper, cellulose- diethylenetriamine, polyacrylamide gel.